Epigenetic changes and functional study of HOXA11 in human gastric cancer. (April 2015) - Cui, Yingying; Gao, Dan; Linghu, Enqiang; Zhan, Qimin; Chen, Runsheng; Brock, Malcolm V; Herman, James G; Guo, Mingzhou
Aim: To examine epigenetic changes and the function of HOXA11 in human gastric cancer (GC).Materials & methods: Seven GC cell lines, five cases of normal gastric mucosa and 112 cases primary GC samples were used in this study.Results: Expression of HOXA11 and lack of promoter region methylation were found in NCI-N87, MKN45, BGC823 and HGC27 cells. Loss of expression and complete methylation were found in AGS gastric cancer cells. Reduced expression and partial methylation were found in MGC803 and SGC7901 cells. Restoration of HOXA11 expression was induced by 5-aza-2′-deoxycytidine. HOXA11 was methylated in 81.25% (91/112) of primary GCs. The presence of methylation was associated with male gender, tumor size, tumor differentiation and lymph node metastasis (all p < 0.05). Restoration of HOXA11 expression reduced cell proliferation, invasion, migration and induced apoptosis and G2/M phase arrest. HOXA11 was found to inhibit Wnt signaling by upregulating NKD1 expression.Conclusion: Epigenetic silencing of HOXA11 promotes GC proliferation, migration and invasion through activation of Wnt signaling.